Kondisi Sosial dan Politik di Desa yang Bercorak Majemuk - Roin Khasanah; Jusuf Harsono; Yusuf Adam Hilman (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2018)
Regional autonomy has many make a change in the level of village, because in the village looked of Pluralis, so that it will appear the potential problems related to the difference existing, these differences can bring up conflict, so that needs to be done an act of, to resolve potential does. Klepu Village, Sawoo Subdustrict,  Ponorogo Regency is an example of a village that had such as shades of the variation in , there are from the research potential difference in practice political in the village, was triggered by differences of religion that is the Islamic and Christian in a village, even though the conflict does not occur in physical form, however problems appear in line with government remodeling inclined to decentralization